Evaluation of growth of avian mycoplasmas on bile salt agar and in bile broth - Majid, M. Shah; Rosendal, S. (Harcourt Publishers Limited, 1987)
All nine Mycoplasma iowae strains and one strain of M gallinarum grew on 0.05 per cent 'bile' agar medium. The colony size of M iowae on this agar medium was similar to the size obtained on bile-free mycoplasma agar. One strain each of M maculosum, M arginini and M bovis also grew on 0.05 per cent bile agar. However, one strain each of M gallisepticum and M meleagridis were inhibited at this concentration. Six of the nine strains of M iowae were also resistant to 1 per cent 'bile' in broth medium but all were resistant to 0.5 per cent. The resistance of M iowae to 0.5 per cent 'bile' in broth may be a useful characteristic for differentiating it from some of the other avian mycoplasmas